The Relationship between Job Satisfaction and Job Performance: A Study on Sports Industry - Alpaslan Baki Ertekin,; Yeşim Avunduk, (Journal of Educational Issues, 2024)
The aim of this research is to determine the relationship between job performance and job satisfaction of individuals working in the sports industry. The sample of the study consisted of 423 people (317 males and 106 females), who work in the sports industry in Istanbul and selected by purposeful sampling method. In the study, in addition to the personal information form, the “Minnesota Job Satisfaction Scale” developed by Weiss et al. (1967) and adapted to Turkish by Baycan (1985), the “Job Performance Scale” developed by Kirkman and Rosen (1999) to determine the job performance of employees and adapted to Turkish by Çöl (2008) were used as data collection tools. In the analysis of the data, independent t-test, ANOVA and Pearson Correlation analyses were performed. The results of the analysis determined that individuals did not differ according to their gender in both their job satisfaction levels and their job performance. It was determined that there was a significant difference in the “External Satisfaction” sub-dimension of the job satisfaction scale according to marital status, and there was a statistical difference in the “Internal Satisfaction” and “External Satisfaction” sub-dimensions of the job satisfaction scale according to the working hours of the participants in the workplace. Moreover, it was determined that there was no significant difference according to the marital status of the participants and the duration of their work. Finally, it was determined that there was a positive and low-level relationship between the sub-dimensions of the job satisfaction scale and the job performance scale. As a result, it was determined that the job satisfaction and job performance levels of the individuals differed according to their socio-demographic characteristics, and the higher their job satisfaction, the higher their job performance.